Mechanochemically Synthesised Flexible Electrodes Based on Bimetallic Metal–Organic Framework Glasses for the Oxygen Evolution Reaction. Issue 4 (25th November 2021) - Lin, Rijia; Li, Xuemei; Krajnc, Andraž; Li, Zhiheng; Li, Mengran; Wang, Wupeng; Zhuang, Linzhou; Smart, Simon; Zhu, Zhonghua; Appadoo, Dominique; Harmer, Jeffrey R.; Wang, Zhiliang; et al.
Abstract: The melting behaviour of metal–organic frameworks (MOFs) has aroused significant research interest in the areas of materials science, condensed matter physics and chemical engineering. This work first introduces a novel method to fabricate a bimetallic MOF glass, through melt‐quenching of the cobalt‐based zeolitic imidazolate framework (ZIF) [ZIF‐62(Co)] with an adsorbed ferric coordination complex. The high‐temperature chemically reactive ZIF‐62(Co) liquid facilitates the formation of coordinative bonds between Fe and imidazolate ligands, incorporating Fe nodes into the framework after quenching. The resultant Co–Fe bimetallic MOF glass therefore shows a significantly enhanced oxygen evolution reaction performance. The novel bimetallic MOF glass, when combined with the facile and scalable mechanochemical synthesis technique for both discrete powders and surface coatings on flexible substrates, enables significant opportunities for catalytic device assembly. Abstract : Bimetallic Co–Fe MOF glass was fabricated via post‐synthetic adsorption of ferric coordination complex on ZIF‐62(Co) followed by vitrification. The presence of bi‐metal ions within the framework significantly improved the catalytic performance of the MOF glass. Then durable MOF glass electrodes were fabricated with ball milling for scalable electrocatalytic devices.